O design do livro didático de alfabetização: tipografia e legibilidade - Luiz Augusto do Nascimento (2011)
In this research about typography and legibility in didactic books for teaching how to read and write we have investigated the relationship between graphic-editorial aspects (especially the typographic ones) and the pedagogical aspects within the activities presented in the books which were approved by PNLD 2010. In order to conduct this line of investigation, two types of document were analyzed: the PNLD Guide and its evaluation records and two collections out of the 19 approved by the Program: Collection Project Prose, published by Saraiva, and Collection L.E.R., published by FTD. The first collection was considered suitable for a graphic project favorable to learning, whereas the second presented an unfavorable graphic project, based on their basic characteristics related to visual composition information hierarchy, contrast and legibility. The present research established connections with Isabel Frades studies on the relationship between graphic and pedagogical aspects in the books for teaching how to read and write, Celia Belmiros on the relationship between verbal texts and images in booklets used for teaching how to read and write, Cyril Burt and Miles Tinkers on legibility, Marshall Lee and Richard Hendels on book design, among others. François Richaudeaus studies on legibility and production of didactic books were used as our theoretical reference. In the collections analyzed the reading protocols present in the activities layout were investigated; the construction of a layout bearing in mind the visual comfort of the student; the typography in relation to the work concept and the proposed activities; the length of the texts used for reading activities; the font size varying according to information hierarchy and target reading public; the combination of font colors and pages related to good contrast to favor legibility. A huge graphic disparity was found between the two analyzed collections. One of them possesses the characteristics which enable handling as well as the fullfilment of the proposed activities. However, the other collection presents a significant amount of graphic inadequacies, such as: long texts, images without context, varied font sizes, confusing layout, fails at offering enough space for developing the activities, conflicting highlight resources, among others. We would like to emphasize the fact that both collections make use of texts written only in capital letters, which is harmful to legibility according to the theoretical discussion presented in our research. The pedagogical contribution of this work is due, mainly, to the discussion and elucidation of graphic-editorial aspects. The research reveals the need for a careful dialog between professionals in the graphic and pedagogical areas when evaluating and developing didactic books.